2022
DOI: 10.1037/emo0001010
|View full text |Cite
|
Sign up to set email alerts
|

Tears do not influence competence in general, but only under specific circumstances: A systematic investigation across 41 countries.

Abstract: In Press at Emotion. This paper is not the copy of record and may not exactly replicate the authoritative document published in Emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The newly created set of vignettes can serve as stimulus material for the experimental manipulation of the emotional basis of tears. The use of this set may allow for the detailed investigation of the issue, moving away from its broadly understood negative and positive causes (Wróbel et al, 2022;Zickfeld et al, 2021) to emotions such as joy/happiness, sadness, anger, fear, that is, emotions that differ not only in valence but also in their social meaning (Fischer & Manstead, 2008). Moreover, it may indicate qualitative differences in reasons for crying dictated by different emotional backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The newly created set of vignettes can serve as stimulus material for the experimental manipulation of the emotional basis of tears. The use of this set may allow for the detailed investigation of the issue, moving away from its broadly understood negative and positive causes (Wróbel et al, 2022;Zickfeld et al, 2021) to emotions such as joy/happiness, sadness, anger, fear, that is, emotions that differ not only in valence but also in their social meaning (Fischer & Manstead, 2008). Moreover, it may indicate qualitative differences in reasons for crying dictated by different emotional backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is assumed that five categories account for most crying triggers in daily life. Experimental approaches have already demonstrated that impression formation processes in response to tearful versus tearless targets are qualified by the triggering reason (e.g., Wróbel et al, 2022), but an externally valid perspective involving the full range of possible crying triggers is lacking (MacArthur & Shields, 2019).…”
Section: Emotional Cryingmentioning
confidence: 99%
“…First, we were interested in the characteristics of the crying episodes and examined who has typically observed crying (Studies 1 and 2), what emotion expressions are paired with crying (Studies 2 and 3), how intense these expressions are (Studies 2 and 3), and which aspects of crying are typically involved, that is, tears, crying-related facial expressions, gestures, and vocalizations (Study 3). Second, we examined how crying individuals are perceived and reacted to; specifically, we examined how crying individuals are perceived on the two core dimensions of impression formation, that is, warmth and competence (e.g., Cuddy et al, 2008), dimensions that are typically examined in the crying literature (e.g., Van de Ven et al, 2017; Wróbel et al, 2022; Zickfeld & Schubert, 2018; Zickfeld et al, 2021; Studies 1–3). We tested whether impression formation depended on the reason triggering crying (Studies 1 and 2).…”
Section: Emotional Cryingmentioning
confidence: 99%
“…In turn, perceptions of helplessness mediate between people's observation of tears in others' faces and their motivation to help these individuals (Vingerhoets et al, 2016). Tearful individuals also appear less competent; people perceive them as having low ability to act in particular situations (Wróbel et al, 2022). In the workplace, tearing elicits disapproval from coworkers (Hoover-Dempsey et al, 1986) rather than the positive responses that tears elicit in other contexts (e.g., Hendriks & Vingerhoets, 2006), perhaps because apparent incompetence and appeals for help violate the implicit contractual notion that individual compensation requires the individual to pull his own weight.…”
Section: Receivers' Responses To Benefit-triggered Tears In Othersmentioning
confidence: 99%